Spatial and Temporal Genetic Diversity of the Peach Potato Aphid Myzus persicae (Sulzer) in Tunisia - Amen Hlaoui; Sonia Boukhris-Bouhachem; Daniela A. Sepúlveda; Margarita C.G. Correa; Lucía M. Briones; Rebha Souissi; Christian C. Figueroa (Insects, 2019)
The peach potato aphid, Myzus persicae (Sulzer), is a worldwide pest of many crops, and the most important aphid pest of peach and potato crops in Tunisia, mainly due to virus transmission, for which insecticides are frequently applied. We studied the genetic structure of M. persicae populations in Tunisia, in order to further our understanding of the biotic and abiotic factors shaping populations and to predict their evolutionary responses to the present management practices. We monitored peach orchards and seed potato crops in different seasons and regions from 2011−2013 and in 2016 (19 populations), assessing the genetic diversity of M. persicae at six microsatellite loci. Temporal and spatial changes in the frequency and distribution of 397 genotypes in 548 sampled aphids were studied. Only 37 genotypes were found more than once (clonal amplification), as most genotypes were found only once (91.60% in peach; 88.73% in potato crops). A similarly high genetic diversity was observed in aphids sampled from peach (G/N = 0.76; Ho = 0.617) and potato (G/N = 0.70; Ho = 0.641). Only a weak genetic differentiation among populations was found, mainly between geographic locations. Clustering analysis revealed genotypes to be grouped mainly according to host plant. The availability of the primary host, high proportion of unique genotypes, high genetic diversity and lack of structuring suggest that the aphid reproduces mainly through cyclical parthenogenesis in Tunisia. On the other hand, we provide a farm-scale study that shows how easily M. persicae can colonize different areas and hosts, which may have important implications in relation to plant virus vectoring.